Obvious child [videorecording (DVD)] - Robespierre, Gillian; Slate, Jenny, 1982-; Lacy, Jake; Hoffmann, Gaby, 1982- (A24, 2014)
Donna Stern is a Brooklyn comedian who gets heartlessly dumped by her two-timing boyfriend. While trying to drown her troubles at the stand-up comedy club, she has a drunken one night stand with a cute young professional named Max (who's not even remotely her type) and ends up pregnant. Donna has to do what is expected of a "responsible adult" just in time for the best/worst Valentine's Day of her life.